Separating habit and recollection in young and elderly adults - Hay, Frances Janine (My University, 1997)
Memory slips are errors in performance that result when an automatic basis for responding (e.g., habit) opposes recollection for a prior event. Prior research has focused on factors that influence the probability of a memory slip while neglecting factors that facilitate performance. Using an extension of Jacoby's (1991) process-dissociation procedure, performance was examined in both a memory slip and a facilitation condition, revealing the separate contributions of habit and recollection. Results showed that manipulating the strength of habit affected estimates of habit but left recollection unchanged (Experiment 1). In contrast, manipulations of presentation rate and response time selectively influenced recollection (Experiments 2-3). Such results support a model of memory in which automatic and consciously controlled influences make independent contributions to performance. The process-dissociation procedure was also used to examine the effects of aging on habit and recollection. It was shown that elderly adults produced more memory slips than young adults but also performed more poorly in a facilitation condition (Experiments 4 & 7). These results demonstrated age-related impairments in recollection in the presence of intact automatic responding. A similar pattern of results was observed using self-report measures of memory (Experiment 7). Older adults were also less able than the young to exploit distinctive contextual information to enhance their ability to recollect (Experiment 4). However, given more supportive study and retrieval conditions, elderly adults were able to benefit from distinctive contextual information at a level comparable to the young (Experiments 5 & 6). Quantitative and qualitative age-related deficits in recollective abilities are interpreted within a dual-process model of memory (e.g., Jacoby, 1991). The problem of distinguishing between a deficit in recollection and a deficit in inhibitory processes in older adults (e.g., Hasher & Zacks, 1988) is discussed, as is the importance of this distinction for purposes of repairing memory performance.
Keywords: Psychology; Psychology